VLSI-Based Electronic Voting Machine (International Journal of Innovative Research in Engineering & Management, 2023)
Voting in the paper was a time consuming and erroneous process. Voting by electronic  voting machine (EVM) is a simple, secure, and time saving technology. The proposed paper consists of the  parties assigned to the election can be represented in the  box along with the total number of contestants  participating in the election process. Ahdar Biometric is  also included in the machine which is a key role paid to  avoid fraudulent voters and to prevent fraud. In the voting  process begins when a voter votes for a particular party  through the adhar bio metric process after the buzzer will  display a notification of who voted for the party displayed  on the screen. After the completion of the voting process  the votes are confirmed by comparing the votes cast with  the contestants in their respective The proposed method  is usefull for college level to all election boards and  digital voting system for real-time applications ranging  from community college elections to university level  elections, as it has the advantage of being able to be re programmed to perform different functions according to  the user's wishes, which helps to reduce prevalence.  expenditures.
Keywords: VHDL; FPGA LCD Display; Adhar Bio metric; Voting Machine